(untitled) (Research, Society and Development, 2021)
Introduction: Garlic (Allium sativum) belongs to the Liliaceae family, its popular knowledge is mainly due to its use in cooking, but there are several alternatives for medicinal use, being researched as a natural and effective alternative against various pathogenic microorganisms. Its efficiency has been evidenced as antifungal, antibacterial, antiviral and antiparasitic. Objective: To evaluate the antimicrobial activity of garlic (Allium sativum), in natura and the aqueous extract, against the fungus Candida albicans, and the bacteria Staphylococcus aureus ATCC 25923 and Streptococcus pyogene 1033B. Method: This is an experimental research with quantitative approach on the evaluation of the antimicrobial activity of garlic extract (Allium sativum, Liliaceae), in natura, and aqueous garlic extract. The agar diffusion method was used - Disc and Well technique in Mueller Hinton Agar medium containing the tested microorganisms, the wells and the filter paper discs containing the extracts. The raw extract was obtained by maceration and the aqueous extract was obtained by soaking the garlic in 0.9% Sodium Chloride for 24 hours for seven days. Results: The numerical results obtained by measuring the halos after the Disc and Well Test showed that the aqueous extract did not inhibit the growth of microorganisms, while the in natura extract through the disc test, obtained significant result against S. aureus, S. pyogenes and C. albicans, possessing halo of inhibition of 23.3 ± 0.6, 20 ± 2 and 18 ± 0 respectively. In the well technique, the halos for S. aureus, S. pyogenes and Candida albicans, were 41.3 ± 0.6, 32 ± 2 and 24 ± 0.6 respectively. Conclusion: It is concluded that the study corroborates in the proof of the antimicrobial action of garlic and shows that the halo of inhibition of the extract in natura both in S. aureus as in S. pyogenes was superior to the halo of the antibiotics tested, the halo presented in Candida albicans was also considerable and bigger than the one presented by the antifungal, showing this way how the microorganisms are sensitive to the extract in natura of garlic in comparison to the antibiotics commonly used.